Nos caminhos das águas: conhecimento ecológico tradicional, recursos naturais e organização de pescadores e pescadoras da Várzea Amazônica, Santarém, Pará, Brasil - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
This study addresses social, economic, organizational, and environmental issues involving artisanal fishermen and women from PAE Aritapera, located in Santarém, Pará. The activity of artisanal fishing has been developed by humanity since the beginning, being considered as the most important source of protein in families living on the banks of rivers in the Amazon basin. Furthermore, this activity plays a significant role in the economic, social, environmental, and cultural dynamics in the lives of families who depend on fishing resources for their survival in floodplain communities. The relationship between people and the natural resources existing within this territory contributes to the formation of the identity and way of life of these populations. Given this reality, this thesis aimed to analyze the traditional ecological knowledge of fishermen and women regarding the use and management of natural resources and the conservation of the floodplain ecosystem in Santarém, Pará. The specific objectives were: a) to analyze the practices of environmental conservation transmitted from the traditional ecological knowledge of fishermen, in light of scientific literature; b) to analyze the process of implementing the land regularization policy, pointing out the socioenvironmental advances and obstacles of agroextractive settlements in the floodplain region of the municipality of Santarém, Pará; c) to identify the different forms of existing social organization, as well as their contribution to actions for the sustainable use of natural resources in the communities studied; d) to investigate how traditional ecological knowledge is transmitted between fishermen and fisherwomen in the family environment, with an emphasis on the use, management, and conservation of natural resources in the floodplain; e) to identify the social and political organization networks of fishermen and fisherwomen in the PAE Aritapera communities and; f) to describe the dynamics used by fishermen during the high and low tide periods. Field data were collected between May 2022 and May 2023, with the target audience consisting of 106 artisanal fishermen residing in the following communities: Costa do Aritapera, Água Preta, Carapanatuba, and Centro do Aritapera, located in the Agroextractivist Settlement Project (PAE) Aritapera in Santarém, Pará. The results revealed that fishermen have extensive traditional ecological knowledge about the natural resources existing in their communities, especially fishing grounds. This knowledge has contributed to the development of local strategies for ecosystem conservation in the floodplain region. Furthermore, this category builds and is part of networks of social and political organizations that help them achieve the implementation of public policies for their territory, as well as contribute to the planning, management, and conservation of natural resources, especially fishing. within the communities of this agroextractivist settlement. Among the actions resulting from this knowledge, community agreements are constructed and agreed upon within community and inter-community meetings. Traditional ecological knowledge is full of symbolism and a sense of belonging, preserved throughout its histories and practices in artisanal fishing that enable the contemplation of the territory and the entire cultural environment, ingrained in the way of life of this category through fishing in the communities studied. This fishermen contributes to the (re)construction of public policies that value this knowledge so that they are appropriate for the Amazon floodplain region.
Keywords: Etnociência; Pescadores artesanais; Ecossistema; Amazônia; CNPQ:: CIENCIAS AMBIENTAIS; Gestão do Conhecimento e Inovação para o Desenvolvimento Sustentável.